Chemical modification of the surface of alumina with alkaline earth metal oxides using the polymeric precursor method for catalysis application - Maciel, A. P.; Tavares, M. H. A.; Melo, R. S.; Silva, F. C.; Soledade, L. E. B.; Dalmaschio, C. J.; Leite, E. R.; Longo, E. [UNESP] (Associação Brasileira de Cerâmica, 2014)
In this study, modifications of alumina surface with of alkaline earth metal oxides were studied, using the polymeric precursor method. The modified compounds were characterized by X-ray diffraction, nitrogen adsorption-desorption and scanning electron microscopy. The catalytical properties of these new catalysts were evaluated for the transesterification reaction of babassu oil. It is observed that the transesterification reaction of babassu oil with methanol was successfully carried out using the modified alumina samples.

Neste trabalho foram estudadas modificações da superfície de alumina com óxidos de metais alcalino-terrosos, usando o método dos precursores poliméricos. Os compostos modificados foram caracterizados por difração de raios X, adsorção-dessorção de nitrogênio e microscopia eletrônica de varredura. As propriedades catalíticas desses novos catalisadores foram avaliadas para a reação de transesterificação de óleo de babaçu. Foi observado que a reação de transesterificação de óleo de babaçu com metanol ocorreu com sucesso na presença das aluminas modificadas.
Modificação química da superfície de alumina com óxidos de metais alcalino-terrosos usando o método do precursor polimérico para aplicação em catálise
Keywords: modificação de superfície; alumina; óxidos de metais alcalino-terrosos; surface modification; alumina; alkaline earth metal oxides